Evaluating High School Students' Ability in Physics Through Self-Assessment in PBL-Based Learning - Natasya Safira Putri; Zainuddin, Abu (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2025)
This study aims to describe the results of self-assessment in PBL-based learning of mechanical wave material to evaluate students' abilities in carrying out PBL learning activities. This type of research is a mixed-method study with two research methods, namely quantitative and qualitative, and then conclusions are drawn. The data from this study are the results of the pre-test and post-test of critical thinking skills, Self-Assessment assessments. The results of applying self-assessment in PBL-based learning were analyzed to determine the impact on PBL-based learning achievements. Additionally, the pre-test and post-test results of critical thinking skills were analyzed using the Wilcoxon Signed Rank Test to identify significant differences in average and n-gain. From this study, PBL-based Self-Assessment using an assessment instrument in the form of an assessment sheet showed that it could be used optimally in evaluating students' abilities in carrying out PBL learning activities. With the highest student completion in the cycles of “conducting individual and group investigations” and “analyzing and evaluating the problem-solving process,” as many as 91.6% or 33 students.